1938
DOI: 10.1590/s0074-02761938000400005
|View full text |Cite
|
Sign up to set email alerts
|

Biologia do saguirú (Characidae, Curimatinae)

Abstract: In Brazil all the fishes belonging to the sub-family Curimatinae are called « saguirú ». The present work gives a biological study of the Curimatus elegans Steind., a small fish without any economical importance, which is to be found along the whole brazilian coast, down till Paraguay. The specimens utilized for the present study come from Fortaleza (Ceará, north-eastern Brazil). The C. elegans is « ilyophagus », that means, it feeds itself exclusively with those organic materials to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
2

Year Published

1989
1989
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
3
0
2
Order By: Relevance
“…The Curimatidae species seems to have a long reprOductive period as a characteristic, since the same results have been found by other authors (AZEVEDO et al 1938;MORAES et al 1984;ROMAGOSA et al 1984;CARVALHO 1984;HARTZ & BARBIERI 1994). The absolute fecundity (F), defined as the number of ovocytes that can be eliminated by female during a stage of posture, presented a mean value of 36608 oocytes, with values ranging from a minimum of 12519 to a maximum 56040.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The Curimatidae species seems to have a long reprOductive period as a characteristic, since the same results have been found by other authors (AZEVEDO et al 1938;MORAES et al 1984;ROMAGOSA et al 1984;CARVALHO 1984;HARTZ & BARBIERI 1994). The absolute fecundity (F), defined as the number of ovocytes that can be eliminated by female during a stage of posture, presented a mean value of 36608 oocytes, with values ranging from a minimum of 12519 to a maximum 56040.…”
Section: Resultssupporting
confidence: 83%
“…Studies of the reproduction of some species ofCurimatidae can be found in AZEVEDO et al (1938), NOMURA & TAVElRA (1979), NOMURA & HAYASHI (1980), TAPHORN & LILYSTRON (1983), CARVALHO (1984), MORAES et al (1984) and ROMAGOSA et al (1984). It must be pointed out the works on C. voga carried out by HARTZ & BARBIERI (1994) and in isolated lagoons of Rio Grande do SuI.…”
mentioning
confidence: 99%
“…observ.). The utilization of that food source by at least some curimatids is also indicated by the food item studies of various authors (Azevedo et al, 1938;de Godoy, 1975;Nomura and Hayashi, 1980;Nomura and Taveira, 1979). Thus Reid's hypothesis of a particleprecipitating mucus system in some Old World Ostariophysan groups is apparently also applicable to the Curimatidae, paralleling the system used by some microphytophagous cichlid fishes (Moriarty et al, 1973) and some anuran tadpoles (Wasserzug, 1972).…”
Section: Ulmentioning
confidence: 85%
“…Alimenta-se de lodo, algas, perifiton e detritos orgânicos, sendo considerada espécie de regime alimentar especializado, do tipo iliófago (Azevedo & Vieira, 1938;Leite et al, 1988;Fugi & Hahn, 1991).…”
unclassified